12-(4-Chlorophenyl)-7-methyl-10-phenyl-3,4,5,6,8,10-hexaazatricyclo[7. 3.0.0(2,6)]dodeca-1(9),2,4,7,11-pentaene - Shah, R.D.; Jotani, M.M.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The 12 non-H atoms defining the triple-fused-ring system in the title compound, C19H13ClN6, are almost coplanar (r.m.s. deviation = 0.023 angstrom). The chloro-substituted ring is almost effectively coplanar with the central atoms [dihedral angle = 6.74 (13)degrees], but the N-bound benzene ring is not [dihedral angle = 54.38 (13)degrees]. In the crystal, supramolecular chains along the a axis sustained by C-H center dot center dot center dot pi and pi-pi [centroid-centroid distance between N4C and C4N five-membered rings = 3.484 (2) angstrom] stacking occur. A very long C-Cl center dot center dot center dot pi contact is also seen.